Biochemical and Hormonal Alterations in Toxoplasma Gondii-Infected Women: Evidence from Kirkuk City, Iraq - Hashim, Dalia Sudad (American Journal of Biodiversity, 2025)
Toxoplasmosis is a zoonotic disease caused by an obligate intracellular parasite, Toxoplasma gondii, that infects all warm-blooded animals except insects and the definitive host is members of the family Felidae. The present study was designed to assess the effect of T. gondii infection on some biological and biochemical markers (dopamine, oxytocin, adiponectin, and chemerin) and also lipidogram parameters including lipid profile, Ca and Cu. During the period between 1st of June to 1th of July 2024, 50 of infected women and 30 of healthy controls were enrolled in Al-Jumhuri General Hospital, Kirkuk city. Results: The level of oxytocin, adiponectin, chemerin, total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), and very low density lipoprotein (VLDL) and dopamine were significantly high in the patients infected while triglycerides (TG), low density lipoprotein cholesterol (LDL-C), calcium, and copper were significantly low in infected patients (P ≤ 0.05).These results show that T. gondii infection induces major changes in neuroendocrine control, regulation of adipokines, and lipid–mineral metabolism during toxoplasmosis, emphasizing the relevance of these biomarkers on diagnosis and comprehension about T. gondii infection.